2009
DOI: 10.3233/wor-2009-0903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of forearm support provided by the Workplace Board on perceived tension, comfort and productivity in pregnant and non-pregnant computer users

Abstract: The aim of the study was to evaluate the effect of forearm support provided by the Workplace Board on perceived tension, comfort and productivity among pregnant and non-pregnant female computer workers. Ten pregnant and 18 non-pregnant women participated in the study. Participants completed three sets of tension/discomfort questionnaires at two week intervals. The first set was completed prior to any workstation intervention; the second set was completed after two weeks working with an ergonomically adjusted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Insufficient blinding of the assessors and/or the participants was observed in several studies [59-61,63,64,69,70,72,75,79-81,83-85,88-91]. Information bias is likely in a number of the studies as some of the data collection tools have not been shown to be reliable and valid [59,61,63-65,72,78-82,85,87-90]. Finally, various studies did not adequately report withdrawal and/or drop-out rates, or had unacceptably high rates (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient blinding of the assessors and/or the participants was observed in several studies [59-61,63,64,69,70,72,75,79-81,83-85,88-91]. Information bias is likely in a number of the studies as some of the data collection tools have not been shown to be reliable and valid [59,61,63-65,72,78-82,85,87-90]. Finally, various studies did not adequately report withdrawal and/or drop-out rates, or had unacceptably high rates (i.e.…”
Section: Discussionmentioning
confidence: 99%